(untitled) (Bangladesh Journal of Medical Science, 2021)
Background: In addition to its impact on public health, COVID-19 has had a major impact on the Indian economy and the employment and education on the field of environmental sciences and engineering. This survey study has a mission to focus on how COVID-19 affects PAN India employment and the likely impact on education on the different environmental fields. Methodology: We have surveyed on PAN India basis by considering different working sectors on environmental field. In our survey, questionnaires circulated by email and different social media like Facebook, WhatsApp and their opinion have been analyzed by analyzing the frequency of the words from their texts / Word Cloud Analysis. Results and Conclusion: This survey report convey highest frequency of the word “life”, “affecting”, “Covid”, “work” which is similar with “job”, “time” “day”, “home”, “very”, “lockdown” by all environmental professionals, students and researchers. This study suggests a need for more comprehensive and longitudinal evaluation of population needs, allowing the country to design holistic initiatives for affected people. Bangladesh Journal of Medical Science Vol.20(2) 2021 p.414-419